Chronic Obstructive Pulmonary Disease in Women. Issue 2 (2007) - Laviolette, Louis; Lacasse, Yves; Doucet, Mariève; Lacasse, Miriam; Marquis, Karine; Saey, Didier; Leblanc, Pierre; Maltais, François
Abstract : BACKGROUND: Little is known about the comparative impact of chronic obstructive pulmonary disease (COPD) between women and men and about women's response to pulmonary rehabilitation. OBJECTIVES: To compare lung function, disability, mortality and response to pulmonary rehabilitation between women and men with COPD. METHODS: In the present retrospective study, 68 women (mean age 62.5±8.9 years) and 168 men (mean age 66.3±8.4 years) were evaluated by means of pulmonary function testing and an incremental symptom-limited cycle exercise test. Forty women and 84 men also participated in a 12-week pulmonary rehabilitation program. A 6 min walking test and the chronic respiratory questionnaire were used to assess the effects of pulmonary rehabilitation. Survival status was also evaluated. RESULTS: Compared with men, women had a smaller tobacco exposure (31±24 versus 48±27 pack-years, P<0.05), displayed better forced expiratory volume in 1 s (44±13 versus 39±14 % predicted, P<0.05), a higher functional residual capacity (161±37 versus 149±36 % predicted, P<0.05) and total lung capacity (125±20 versus 115±19 % predicted, P<0.001). Peak oxygen consumption was not different between women and men when expressed in predicted values but lower in women when expressed in absolute values. Pulmonary rehabilitation resulted in significant improvements in 6 min walking test and quality of life in both sexes, but women had a greater improvement in chronic respiratory questionnaire dyspnea. Survival status was similar between sexes, but predictors of mortality were different between sexes. CONCLUSIONS: Women may be more susceptible to COPD than men. The clinical expression of COPD may differ between sexes with greater degree of hyperinflation in women, who also benefit from pulmonary rehabilitation.